197k views
0 votes
2 +5k = 3k -4 -2help piz

User Emaxsaun
by
5.9k points

1 Answer

1 vote

Answer:

k=−4

Explanation:

Let's solve your equation step-by-step.

2+5k=3k−4−2

Step 1: Simplify both sides of the equation.

2+5k=3k−4−2

2+5k=3k+−4+−2

5k+2=(3k)+(−4+−2)(Combine Like Terms)

5k+2=3k+−6

5k+2=3k−6

Step 2: Subtract 3k from both sides.

5k+2−3k=3k−6−3k

2k+2=−6

Step 3: Subtract 2 from both sides.

2k+2−2=−6−2

2k=−8

Step 4: Divide both sides by 2.

2k/2=−8/2

k=−4

User Nabmeister
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.